Peningkatan Fasilitas Desa Berupa Sarana Informasi Arah Melalui Pemasangan Plang Arah Jalan di Desa Taji - Hanif, Muhammad; Khusna, Amira; Aulia, Adinda (Bakti Insani: Jurnal Pengabdian dan Pemberdayaan, 2025)
The Community Service Program (KKN) is a form of implementation of the Tri Dharma of Higher Education, particularly in the field of community service. In 2025, KKN students from group 118 of Raden Mas Said State Islamic University of Surakarta implemented the program in Taji Village, Juwiring District, Klaten Regency. The main problem faced by the village was the lack of directional facilities, which often caused difficulties for residents and visitors in finding the location. This KKN program focused on the creation and installation of road signs using a participatory method involving students, village officials, and the community. The activity stages included a site survey, creating the sign design, the production process in collaboration with local MSMEs, painting, and installation at strategic points. The program results showed increased accessibility, ease of mobility, and strengthening of village identity through the availability of road signs. In addition, this program succeeded in encouraging community participation and had a positive impact on the development of village infrastructure